2020
DOI: 10.1038/s41598-020-68950-y
|View full text |Cite
|
Sign up to set email alerts
|

KRAS(G12C)–AMG 510 interaction dynamics revealed by all-atom molecular dynamics simulations

Tatu Pantsar

Abstract: The first KRAS(G12C) targeting inhibitor in clinical development, AMG 510, has shown promising antitumor activity in clinical trials. On the molecular level, however, the interaction dynamics of this covalently bound drug-protein complex has been undetermined. Here, we disclose the interaction dynamics of the KRAS(G12C)-AMG 510 complex by long timescale all-atom molecular dynamics (MD) simulations (total of 75 μs). Moreover, we investigated the influence of the recently reported post-translational modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 52 publications
(67 reference statements)
4
20
0
Order By: Relevance
“…During the development of sotorasib, structural improvements in the quinazoline scaffold to leverage the cryptic pocket formed by H95, Y96, and Q99 in the a3helix of the GDP-KRAS G12C protein produced potent pharmaceutical properties. 18 Pantsar 40 recently reported that Y96 of KRAS G12C forms p-p-stacking, a noncovalent intermolecular interaction between aromatic rings; in addition, R68 formed cation-p interactions, which are derived from an electrostatic interaction between a cation and adjacent electron-rich compounds, with the azaquinazoline base of sotorasib in a molecular dynamics simulation of the KRAS G12Csotorasib complex. In addition, we found that Y96 is located at the entrance of the hydrophobic pocket, where sotorasib and adagrasib bind with the KRAS G12C protein.…”
Section: Discussionmentioning
confidence: 99%
“…During the development of sotorasib, structural improvements in the quinazoline scaffold to leverage the cryptic pocket formed by H95, Y96, and Q99 in the a3helix of the GDP-KRAS G12C protein produced potent pharmaceutical properties. 18 Pantsar 40 recently reported that Y96 of KRAS G12C forms p-p-stacking, a noncovalent intermolecular interaction between aromatic rings; in addition, R68 formed cation-p interactions, which are derived from an electrostatic interaction between a cation and adjacent electron-rich compounds, with the azaquinazoline base of sotorasib in a molecular dynamics simulation of the KRAS G12Csotorasib complex. In addition, we found that Y96 is located at the entrance of the hydrophobic pocket, where sotorasib and adagrasib bind with the KRAS G12C protein.…”
Section: Discussionmentioning
confidence: 99%
“…In this interaction network, hydrophobic hubs (displaying more than three hydrophobic interactions) include the residues V14 and A146, which when mutated are associated with altered RAS dynamics [106,127]. In another study, MD simulations revealed highly dynamic characteristics for the switches even when there exists a covalent inhibitor beneath the switch-II [128]. Importantly, the inhibitor AMG 510 appeared extremely stable regardless of the switch movements.…”
Section: Ras-uncovering the Conformational Dynamics Of A Challenging mentioning
confidence: 98%
“…Sotorasib is an oral drug that selectively inhibits mutant KRAS G12C by covalently and irreversibly binding to the cysteine in the KRAS G12C transversion, locking the protein in its inactive GDP-bound state ('OFF') (Fig. 2) [78,84,85]. In preclinical testing, sotorasib inhibited ERK phosphorylation and tumor cell growth in multiple KRAS G12C -mutant cell lines in vitro, and in mice with xenografts of human tumor cells [11,86].…”
Section: Sotorasibmentioning
confidence: 99%